Biomonitoring of 2,4,6-trinitrotoluene and degradation products in the marine environment with transplanted blue mussels (M. edulis) - Strehse, Jennifer Susanne; Appel, Daniel; Geist, Catharina; Martin, Hans-Jörg; Maser, Edmund (PANGAEA, 2023)
Blue mussels were exposed in the munitions dumping area Kolberger Heide from 14 December 2016 to 16 March 2017 as part of the UDEMM project. For this purpose, the mussels were attached in small bags to a mooring on the seabed with the help of divers. The mussels were exposed directly on the seabed (position 7U) or one metre from the bottom (position 7O). Samples were analyzed on contents of the energetic compounds (EC) TNT (2,4,6-trinitrotoluene), 2-ADNT (2-amino-4,6-dinitrotoluene), and 4-ADNT (4-amino-2,6-dinitrotoluene).
Keywords: biomonitoring; munitions; Mytilus edulis